Desejo e adolescência: uma perspectiva clínica - Silva, Domenica de Melo (2024)
The research has desire as a guiding thread based on the psychoanalytic clinic with adolescents. It seeks to answer the relationship between the identification process and the assumption of desire in the work of psychically crossing adolescence. This is a critical study, which addresses the elements of historical, social and political content present in this process. The theoretical framework of Freudian and Lacanian Psychoanalysis, as well as its intercessors, is used to work on the categories of adolescence and desire in the context of Modernity. The psychoanalytic method was used, which consists of clinical research work in which the treatment is based and supported by research into the experience of each subject inserted in the social bond, considered as a discursive bond. It aims to bring clinical and social phenomena closer together, in the articulation between individual and society, subjectivity and culture. It starts from the conception of adolescence as a contemporary cultural ideal, with dynamics of identification pointing to the imperative of well-being, fulfillment and happiness, attributes sought by individuals of all ages, resulting in a time extension of this psychic operation. The construction of an ideal self that is impossible to achieve keeps desire alienated from the desire of the Other, through discourses. From this perspective, psychoanalytic ethics is brought as an alternative, as it is based on desire and singularity, by placing lack as necessary for access to the truth, always fictitious, of the subject of the unconscious. The phenomenon of transference is pointed out as a driving force and structuring support within the analytical process, operating in the three registers: in the symbolic through the word, in the real through the hole in the discourse and in the imaginary through identification. A space for the construction and precipitation of desiring subjectivity, it provides symbolization, change in meaning, in discourses and the crossing of the plane of identifications. The analyst's desire appears in its double function, as object a, cause of desire and object of the drive, leading the subject to the articulation of desire. The actualization of unconscious contents in the figure of the analyst functions as a new bond, a new love, the love of transference, which has at its base the transmission of lack, the lack of knowledge and the lack of an object for desire. A relationship of love as meaning, which allows for slippages in the meaning of the ideal, in addition to a possible change in the subject's position, from the desire for recognition to the recognition of desire.